ANALISIS PERAN CUSTOMER SERVICE DI BANK BNI SYARIAH KCP PLERED - Joni Joni; Fikri Putri Diniati (Universitas Siliwangi, 2019)
Customer service plays a very important role in various companies and financial institutions such as Islamic banks. As a Customer Service , the roles and functions must be established. If customer service does not implement one of the functions that should be carried out, it will have an impact on the role of customer service, namely maintaining customers and getting new customers. The role of customer service can be carried out if each of the functions can be implemented by customer service. The purpose of this study was to determine the role of Customer Service at Bank BNI Syariah KCP Plered.The method used in this study is a descriptive method with is qualitative. With two data sources, namely primary data sources consisting of Customer Service, Operational Service Head, several customer security guards and secondary data sources consisting of supporting books, working papers and photos obtained from the field. Data collection techniques used were interviews, observation and documentation. Based on the results research that role customer service at Bank BNI Syariah KCP Plered that is customer service as a service unit able to doing its role that is maintain customer and get customer new in the counter or bank. Implementation role could seen from implementation every the functions contained inside , though there is some functions that are not yet optimal in implementation